2004
DOI: 10.1021/jp0367528
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Heterocyclic Imines as New Potential Nonlinear Optical Materials

Abstract: In the course of a search for new thermostable acentric nonlinear optical crystalline materials, several heterocyclic imine derivatives were designed, with the general structure D−π−A(D‘). Introduction of a donor amino group (D‘) into the acceptor moiety was expected to bring H-bonds into their crystal structures, and so to elevate their melting points and assist in an acentric molecular packing. Six heterocycle-containing compounds of this type were prepared, single crystals were grown for five of them, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…In contrast to methylation, where the first substitution activates additional substitution, Schiff base formation at one nitrogen deactivates the second nitrogen, and only the monoimines form under mild conditions. 3,4 DAMN has also been used to prepare 5,6-dicyanopyrazines, [5][6][7][8][9][10][11][12] purines, 13 and amides. 14,15 The conjugated aldehyde and vinyl group in acrolein lead to reactions that are facile, and often different, from those of other aldehydes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to methylation, where the first substitution activates additional substitution, Schiff base formation at one nitrogen deactivates the second nitrogen, and only the monoimines form under mild conditions. 3,4 DAMN has also been used to prepare 5,6-dicyanopyrazines, [5][6][7][8][9][10][11][12] purines, 13 and amides. 14,15 The conjugated aldehyde and vinyl group in acrolein lead to reactions that are facile, and often different, from those of other aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…(2Z)-2-Amino-3-{[(1E)-2-methylprop-2-en-1-ylidene]amino}but-2-enedinitrile (Methacrodamn) 19 (4). 4 was prepared analogously to 3, using methacrolein in place of crotonaldehyde.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome this limitation many different approaches have been investigated such as use of molecular asymmetry, chirality, hydrogen bonds, strong Coulomb interactions, non-rod-shaped p-conjugated cores, octupolar compounds and photochromism. 2,3 Another interesting approach for achieving acentric crystals is supramolecular synthetic co-crystallization. It offers more design feasibility as one or both constituent molecules can be modified to fit one another and to acquire the desirable macroscopic properties in the solid state.…”
mentioning
confidence: 99%
“…Recently Unver et al have reported the structural and NLO properties for some imine bridged aromatic compounds [13,19,20]. Volodymr et al have designed thermostable acentric nonlinear optical crystalline imine derivatives [21,22]. Heravic et al have reported a theoretical investigation of the structure electronic properties and second harmonic generation of imine ligands [23].…”
Section: Introductionmentioning
confidence: 99%